DINAMIKA GLOBALISASI DAN TRANSIONALISASI HUKUM ISLAM DI NEGARA NOMOKRASI INDONESIA - Muhammad Jumaidi Pamalingan,; Kurniati, Kurniati; Musyfikah Ilyas, (Journal of Innovation Research and Knowledge, 2025)
This study discusses how global currents influence the formation, implementation, and adaptation of Islamic law in Indonesia . The purpose of this study is to analyze how the processes of globalization and transnationalization influence the development and adaptation of Islamic law in Indonesia as a state based on the principle of nomocracy, as well as to identify the challenges faced in integrating Islamic law into the national legal system. The research method used is library research, which involves searching for and collecting data from libraries, such as history books, using a sociological approach to Islamic law. The results of this study demonstrate that globalization is a unique phenomenon in human civilization. Globalization in Islamic law is not only related to external influences but also concerns how Islamic law responds to the challenges and changes of the modern world. Transnationalization creates new space for Islamic law to grow within a country. The dynamics of globalization and the transnationalization of Islamic law demonstrate how Islamic law develops and adapts in an increasingly globally connected world. Several challenges to integrating Islamic law into the legal system arise, including political challenges, legal pluralism, and international resistance to sharia.